Diabetes‐related quality of life is enhanced by glycaemic improvement in older people. Issue 2 (5th November 2014) - Abbatecola, A. M.; Spazzafumo, L.; Fabbietti, P.; Testa, R.; Rabini, R. A.; Bonfigli, A. R.; Corsonello, A.; Lattanzio, F.; Paolisso, G.
Abstract Aims To investigate the validity and reliability of the Audit of Diabetes‐Dependent Quality of Life instrument in older Italians with diabetes and to test the association of diabetes‐related quality of life with glycaemic control over time. Methods A total of 558 outpatients with Type 2 diabetes from the Diabetic Unit of the Italian National Research Centre on Aging Hospital in Ancona were enrolled to complete questionnaires (Audit of Diabetes‐Dependent Quality of Life‐19 and the Short‐Form‐12), and to undergo clinical and biochemical testing at baseline and at 12 months of follow‐up. The overall impact of diabetes using the average weighted impact score from the Audit of Diabetes‐Dependent Quality of Life questionnaire was calculated. Participants were categorized according to this score as having either less or more negative diabetes‐related quality of life. Results Participants had a mean ± sd age of 67.7 ± 9.2 years and 51.8% were male. Factor analysis and Cronbach's coefficient of internal consistency (Cronbach's α = 0.931) confirmed that the 19 domain‐specific Audit of Diabetes‐Dependent Quality of Life items could be combined into a single scale in this Italian population. The impact score correlated with the physical (r = 0.275; P < 0.001) and mental components (r = 0.291; P < 0.001) of the Short‐Form‐12 questionnaire. Significant differences were found according to diabetic complications in specific Audit of Diabetes‐Dependent Quality of Life items and impact scores. Insulin use had a greater association with a more negative quality of life compared with other antidiabetic agents. A multivariate linear regression model with restricted linear spline application showed that the relationship between HbA1c and impact score was not linear and that the change in the impact score was associated with improved glycaemic control in those with a less negative diabetes‐related quality of life at 12 months. Conclusions The Audit of Diabetes‐Dependent Quality of Life‐19 is a valid tool for measuring the impact of diabetes on quality of life in older Italians. Perception of diabetes‐related quality of life is associated with glycaemic control over time.